Impact of pilot-scale processing (thermal, PEF, HPP) on the stability and bioaccessibility of polyphenols and proteins in mixed protein- and polyphenol-rich juice systems. (August 2020) - Stübler, Anna-Sophie; Lesmes, Uri; Juadjur, Andreas; Heinz, Volker; Rauh, Cornelia; Shpigelman, Avi; Aganovic, Kemal
Abstract: Due to health-beneficial effects of polyphenols, their stability and bioaccessibility in strawberry puree as influenced by processing (thermal, pulsed electric field (PEF), high pressure processing (HPP)) and by combination with relatively protein-rich vegetable juice (kale) was investigated. Soluble strawberry anthocyanins decreased in the presence of kale, in a processing-dependent manner, likely due to interactions with kale proteins. In the strawberry-water-system, polyphenols increased after processing due to increased extraction, especially after thermal and PEF, while in the mix anthocyanins increased especially after HPP and PEF. Anthocyanin structure affected the ratio of free anthocyanins after the interaction. During gastric digestion, an increase in bioaccessible anthocyanins was observed, while during intestinal digestion it strongly diminished. Thermal, PEF and formulation of the mix reduced soluble protein fractions, as observed by decreasing SDS-PAGE band intensity. The proteins were easily digestible and after 15 min of gastric digestion, no bands appeared with an increase in TCA soluble peptides. Industrial relevance: With the increase in health awareness and the changing on-the-go lifestyle, consumers demand convenient fruit and vegetable-based products with high nutritional and health-promoting content. Thus, utilization of alternative processing with minimal impact on the quality of fruit and vegetable juices is considered as a promising tool to deliver such high nutritional products, however, little is known about their effect on multi-component juice systems, where interactions between the different components can occur. Strawberries are the most commonly consumed berry type, delivering high quantities of polyphenols and therefore a representative polyphenol-rich model system. Kale is gaining increasing attention due to the nutritional profile, above others, it contains relatively (to other fruits and vegetables) high protein content, and therefore displays an interesting vegetable-based protein-rich model. A more in-depth understanding of the effect of alternative processing on polyphenol-protein interactions in these increasingly popular mixed systems (green smoothies) and the digestive fate of these potentially health-beneficial compounds is studied and provides new insights into designing functional products attractive for consumers. Highlights: Effect of thermal, PEF and HPP and formulation with kale on polyphenols was studied. Soluble anthocyanins decreased in mixed system due to interactions with kale matrix. Extent of interactions was polyphenol structure and preservation technology dependent. During simulated gastric phase high anthocyanin bioaccessibility was observed. Anthocyanin bioaccessibility decreased during the intestinal phase.